Potek in prognoza raka dojk - Čufer, Tanja (Radiology and oncology (Ljubljana), 1998)
Breast cancer is the most frequent cancer of females. While at the beginning of the 20th century this disease was still considered incurable, presently more than 50% of breast cancer patients can be cured by a combination of surgery, irradiation and chemotherapy. The prognosis and course of breast cancer are significantly influenced by the stage of the disease at the beginning of therapy. Patients with lager tumors, and particularly those with axillary lymph node involvement, have a worse prognosis. The course of diseaseand patient's prognosis are further influenced by other tumor characteristics, such as pathohistological type and grande of malignancy, presence of hormone receptors, proliferative potential of cells and others. Last but not least, the course and outcome of the disease are also significantly influenced by therapy. Advanced surgical techniques in combination with radiotherapy enable a better local control of the disease to be achieved by less extensive surgery. Nowadays, breast preservation is feasible on more than a half of all patients. Adjuvant chemotherapy together with local treatment enables a better systemic control of the disease and significantly improves the survival of patients with operable breast cancer. So far, metastatic breast cancer is still considered incurable, however, the disease can be succesfully held under control for a longer period of time. It is expected that the prognosis of breast cancer patients will be furthere improved by new, more effective treatment modalities, as well as by organized screening associated with the earlier breast cancer detection.
Keywords: Breast neoplasms; dojke; Neoplasm staging; Prognosis; prognoza; rak (medicina); Therapy; Treatment outcome; zdravljenje